Por una filosofía política de las desigualdades ecológicas: Leer El ecologismo de los pobres hoy - Charbonnier, Pierre (Conceptos Históricos, 2017)
This paper investigates the work and thinking of economist Joan Martinez Alier. It is an attempt to develop the main idea advocated in The Environment alism of the Poor: the capitalist mode of development and the market-oriented economy not only caused the autonomization of the economy from society, but also disconnected the economy from the basic planetary metabolic regulations. According to Martinez Alier, ecological economics and environmental sociology should then find a common analytical and political ground. Here, we try to understand the epistemological and political implications of this fundamental thesis.